2023
DOI: 10.3390/biomimetics8080571
|View full text |Cite
|
Sign up to set email alerts
|

Vein–Membrane Interaction in Cambering of Flapping Insect Wings

Daisuke Ishihara,
Minato Onishi,
Kaede Sugikawa

Abstract: It is still unclear how elastic deformation of flapping insect wings caused by the aerodynamic pressure results in their significant cambering. In this study, we present that a vein–membrane interaction (VMI) can clarify this mechanical process. In order to investigate the VMI, we propose a numerical method that consists of (a) a shape simplification model wing that consists of a few beams and a rectangular shell structure as the structural essence of flapping insect wings for the VMI, and (b) a monolithic sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Figure 3 shows the finite-element implementation of the proposed IMMW model using linear triangular shell finite elements. The span-wise length L w and the chordwise length C w of the wing are 0.0113 and 0.00311 m, respectively [ 31 ]. These dimensions were taken from a real insect wing.…”
Section: Numerical Implementation Of the Insect-mimetic Micro Wing Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 3 shows the finite-element implementation of the proposed IMMW model using linear triangular shell finite elements. The span-wise length L w and the chordwise length C w of the wing are 0.0113 and 0.00311 m, respectively [ 31 ]. These dimensions were taken from a real insect wing.…”
Section: Numerical Implementation Of the Insect-mimetic Micro Wing Modelmentioning
confidence: 99%
“…In the present study, we propose an IMMW model for FWNAVs based on shape simplification modeling [ 31 ]. In our previous study [ 31 ], we focused on the demonstration of the fundamental validity of this modeling.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early researchers found that the flapping law of different insect populations is essentially a simple harmonic function [ 3 ]. Then, others observed the kinematic parameters of insects in hovering and forward flight states and found that the flapping amplitude of insect wings is approximately between 60° and 180° [ 4 ], the flapping attack angle is 35° or larger [ 5 ], and the flapping frequency is between 25 and 400 Hz [ 6 ]. Upon observing the dynamic deformation of butterfly wings, researchers found that the forewings and hindwings of butterflies are independent and can perform flapping movements asymmetrically [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%